1994
DOI: 10.1002/pro.5560030609
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of staphylococcal nuclease denaturation. I. The acid‐denatured state

Abstract: Using high-sensitivity differential scanning calorimetry, we reexamined the thermodynamics of denaturation of staphylococcal nuclease. The denaturational changes in enthalpy and heat capacity were found to be functions of both temperature and pH. The denatured state of staphylococcal nuclease at pH 8.0 and high temperature has a heat capacity consistent with a fully unfolded protein completely exposed to solvent. At lower pH values, however, the heat capacity of the denatured state is lower, resulting in a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
71
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 43 publications
13
71
0
Order By: Relevance
“…The number of H + that were bound upon thermal denaturation over a range of pH values was lower than the number expected to be bound by the D state if the ionizable groups in this state titrated with the pK a values of model compounds. For example, whereas the data in Figure 1, panel B, show that at pH 7 nearly 1.5 H + are bound preferentially by U relative to N, the DSC experiments (18) showed that only 0.1 H + were bound upon thermal unfolding at this pH. Even at pH values close to pH mid , where the data in Figure 1, panel B, show that nearly 5 H + are bound upon unfolding to the U state, the number of H + bound upon thermal unfolding was only 0.7.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The number of H + that were bound upon thermal denaturation over a range of pH values was lower than the number expected to be bound by the D state if the ionizable groups in this state titrated with the pK a values of model compounds. For example, whereas the data in Figure 1, panel B, show that at pH 7 nearly 1.5 H + are bound preferentially by U relative to N, the DSC experiments (18) showed that only 0.1 H + were bound upon thermal unfolding at this pH. Even at pH values close to pH mid , where the data in Figure 1, panel B, show that nearly 5 H + are bound upon unfolding to the U state, the number of H + bound upon thermal unfolding was only 0.7.…”
Section: Discussionmentioning
confidence: 82%
“…The nativelike H + binding properties of the D state were evident in earlier DSC studies of the pH dependence of thermal unfolding of wild-type SNase, although that was not the interpretation given to those data (18). The number of H + that were bound upon thermal denaturation over a range of pH values was lower than the number expected to be bound by the D state if the ionizable groups in this state titrated with the pK a values of model compounds.…”
Section: Discussionmentioning
confidence: 92%
“…The acid unfolding of SNase is not affected by these factors 32–40. SNase acid unfolds at a relatively high pH, near 4, where intramolecular repulsive interactions in the N state are well balanced by attractive ones.…”
Section: Introductionmentioning
confidence: 95%
“…[27][28][29][30][31] The acid unfolding of SNase is not affected by these factors. [32][33][34][35][36][37][38][39][40] SNase acid unfolds at a relatively high pH, near 4, where intramolecular repulsive interactions in the N state are well balanced by attractive ones. SNase is also devoid of buried basic residues that could promote acid unfolding at this relatively high pH.…”
Section: Introductionmentioning
confidence: 99%
“…Carra and Privalov, proponents of the three state model for solvent denaturation [17], have concluded that thermal denaturation of wild-type nuclease is two state [17,18]. On the other hand, Eftink's group has shown that V66W mutant with tryptophan or tryptophan analogues, appears to be better fit by a three state thermal unfolding model [7].…”
Section: Introductionmentioning
confidence: 99%